Influence of waste vegetable oil biodiesel and hexanol on a reactivity controlled compression ignition engine combustion and emissions. (1st September 2020) - Thomas, Justin Jacob; Sabu, V.R.; Nagarajan, G.; Kumar, Suraj; Basrin, G.
Abstract: In the present work, biofuels produced from agricultural waste have been proposed as a substitute for petroleum-based fuel. Biodiesel produced from waste vegetable oil has been used alongside hexanol in a reactivity controlled compression ignition engine. The waste vegetable oil biodiesel was prepared by trans-esterification and was directly injected inside the cylinder. Hexanol was injected into the port during early suction stroke. A modified 1-cylinder water-cooled diesel engine was used for the tests. The modified engine was tested at medium load and rated load for injection pressures of 400, 500 and 600 bar. The proportion of hexanol to waste vegetable oil biodiesel was also varied to find the optimal combination. The results were mapped and analyzed with diesel operation at similar conditions. A maximum increase of 1.5% in thermal efficiency was observed compared to Diesel. Oxides of nitrogen and smoke emissions reduced simultaneously for biodiesel-hexanol combinations compared to diesel. Injection pressure of 500 bar and hexanol proportion of 30% at medium load and 60% at rated load were found to be optimum concerning lowest emissions. This study proposes that waste vegetable oil biodiesel and hexanol combination in reactivity controlled compression ignition mode can be an effective replacement for conventional fossil fuel. Highlights: Hexanol-Waste cooking oil biodiesel in an advanced combustion engine. Simultaneous reduction of smoke and oxides of nitrogen. Increased thermal efficiency compared to Diesel.